Pelecotoides xui sp. nov., the third Asian species of Pelecotoides Laporte from Xizang, China (Coleoptera: Ripiphoridae: Ptilophorinae) - Wang, Cheng-Bin (Zootaxa, 2026)
Pelecotoides Laporte, 1833 (Coleoptera: Ripiphoridae: Ptilophorinae) is reported from western China for the first time; a new species, P. xui sp. nov., is described and illustrated from Xizang. A key to the three Asian species of Pelecotoides is provided.